2007
DOI: 10.1177/030089160709300304
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Clinical and Pathologic Features in Patients with Glioblastoma Multiforme Treated with Concomitant Radiation plus Temozolomide

Abstract: The results suggest that analysis of prognostic markers in glioblastoma multiforme is complex. In addition to previously recognized prognostic variables such as age and Karnofsky performance score, tumor size, total resection and proliferation index overexpression were identified as predictors of survival in a series of patients with glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…PTEN mutations have been found in 15 to 40% of glioblastoma [26,27]. In several previous studies PTEN mutations were not associated with prognosis of glioblastoma [28,29]. In our series we report 7 missense mutations mostly in the region of homologous tensin, auxlin and dual specificity phosphatases thereby possibly resulting in the gliomogenesis in the samples harboring these mutations.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…PTEN mutations have been found in 15 to 40% of glioblastoma [26,27]. In several previous studies PTEN mutations were not associated with prognosis of glioblastoma [28,29]. In our series we report 7 missense mutations mostly in the region of homologous tensin, auxlin and dual specificity phosphatases thereby possibly resulting in the gliomogenesis in the samples harboring these mutations.…”
Section: Discussionsupporting
confidence: 44%
“…Most of the previous studies concluded that patient's age had the greatest effect on survival. Vittorio Donato in 2007 observed that patients under 61 years of age had a significantly prolonged survival [29]. We observed that Median Overall survival was better i.e, 15 months in patients with KPS >70 compared to 13 (7,19) months in patients with KPS ≤ 70 (p>0.05) .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Of the candidate studies, 13 articles failed to completely describe the available survival data. Finally, 51 published studies in total were included in the analysis after eliminating articles unsatisfying the selection criteria and duplicates (Jaros et al, 1992;Torp et al, 1992;Montine et al, 1994;Ellison et al, 1995;Heegaard et al, 1995;Kros et al, 1996;Coons et al, 1997;Pollack et al, 1997;Dehghani et al, 1998;McKeever et al, 1998;Ritter et al, 1998;Figarella-Branger et al, 2000;Rodriguez-Pereira et al, 2000;Ho et al, 2001;ReaveyCantwell et al, 2001;Zhong et al, 2001;Bredel et al, 2002;Pollack et al, 2002;Bowers, 2003;Chiang et al, 2003;Neder et al, 2003;Wessels et al, 2003;Zamecnik et al, 2003;Preusser et al, 2005;Uematsu et al, 2005;Kleinschmidt-DeMasters et al, 2006;Donato et al, 2007;Kanamori et al, 2008;Kuo et al, 2009;Laks et al, 2009;Li et al, 2009;Armstrong et al, 2010;Nabika et al, 2010;Watanabe et al, 2010;Yoshida et al, 2010;Habberstad et al, 2011;Margraf et al, 2011;Qiang et al, 2011;Shen et al, 2011;Zawrocki et al, 2011;…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…3 In contrast, there are publications opposing a prognostic relevance. 4,5 Currently, the possibility of EGFRtargeted therapies has initiated the development of a variety of agents directed either towards the extracellular ligand-binding domain or the intracellular tyrosine kinase domain including the monoclonal antibody Erbitux (IMC-C225, ImClone/Bristol Myers Squibb), and the EGFR tyrosine kinase inhibitors Gefitinib (ZD1839, Iressa, AtraZeneca) and Erlotinib (OSI-774, OSI/Genentech/Roche). 6 Although these EGFR-targeted therapies are already in phase III clinical trials, it still remains to be determined, which subgroup of patients will most likely benefit.…”
Section: Introductionmentioning
confidence: 99%